2023
DOI: 10.3390/jpm13101497
|View full text |Cite
|
Sign up to set email alerts
|

Non-Ventilated Patients with Spontaneous Pneumothorax or Pneumomediastinum Associated with COVID-19: Three-Year Debriefing across Five Pandemic Waves

Adina Maria Marza,
Alexandru Cristian Cindrea,
Alina Petrica
et al.

Abstract: Spontaneous pneumothorax and pneumomediastinum (SP–SPM) are relatively rare medical conditions that can occur with or independently of COVID-19. We conducted a retrospective analysis of SP–SPM cases presented to the emergency departments (EDs) of two University-affiliated tertiary hospitals from 1 March 2020 to 31 October 2022. A total of 190 patients were identified: 52 were COVID-19 cases, and 138 were non-COVID-19 cases. The primary outcome we were looking for was in-hospital mortality. The secondary outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The presence of a CVC was also proven to be the strongest independent predictor for upper extremity deep vein thrombosis (OR, 7.3; 95% CI, 5.8-9.2) [23]. Kuang et al analyzed 1643 critically ill patients and reported an incidence of symptomatic thrombotic complications of the CVCs of 9.5 per 1000 catheters days [4]. Joks et al reported an incidence of 13.5% of CVC-related VTE in hematological patients [5], whereas in oncology patients, VTE's occurrence appears to range around 5% [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of a CVC was also proven to be the strongest independent predictor for upper extremity deep vein thrombosis (OR, 7.3; 95% CI, 5.8-9.2) [23]. Kuang et al analyzed 1643 critically ill patients and reported an incidence of symptomatic thrombotic complications of the CVCs of 9.5 per 1000 catheters days [4]. Joks et al reported an incidence of 13.5% of CVC-related VTE in hematological patients [5], whereas in oncology patients, VTE's occurrence appears to range around 5% [6].…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, a significant group of patients who are admitted to the ICU and require CVC or CV-HDC placement are those with severe manifestations of COVID-19 disease, who experience respiratory failure, septic shock, multiple organ dysfunction [4]. The hypercoagulable state in patients with SARS-CoV-2 infection is a well-known risk factor for arterial and venous thromboembolism [5], especially in those with advanced vascular access devices [6].…”
Section: Introductionmentioning
confidence: 99%
“…It confronted obstacles in effectively controlling transmission and mitigating the consequences of the disease, encompassing issues related to healthcare infrastructure as well as demographic and societal factors [41]. The literature also shows that severe clinical forms had a markedly higher median duration of disease prior to hospitalisation compared with the mild and moderate forms [42].…”
Section: Comparison Of Covid-19 Pandemic Waves For Pe Groupmentioning
confidence: 99%